Proconvertase Furin Is Downregulated in Postural Orthostatic Tachycardia Syndrome - Spahic, Jasmina Medic; Ricci, Fabrizio; Aung, Nay; Axelsson, Jonas; Melander, Olle; Sutton, Richard; Hamrefors, Viktor; Fedorowski, Artur (Frontiers in Neuroscience, 2019)
Background: Postural Orthostatic Tachycardia Syndrome (POTS) is a cardiovascular autonomic disorder characterized by orthostatic intolerance and high prevalence among young women. The aetiology of POTS is uncertain, though autoimmunity and inflammation may play an important role. We aimed to identify novel inflammatory biomarkers associated with POTS. Methods and Results: In the Syncope Study of Unselected Population in Malmö (SYSTEMA) cohort, we identified 396 patients (age range, 15-50 years) with either POTS (n=113) or normal haemodynamic response during passive head-up-tilt test (n=283). Blood samples were analyzed using antibody-based Proximity Extension Assay technique simultaneously measuring 57 inflammatory protein biomarkers. The discovery algorithm was a sequential two-step process of biomarker signature identification by supervised, multivariate, principal component analysis and verification by univariate ANOVA with Bonferroni correction. POTS patients were younger (26 vs. 31 years; p<0.001) and there was no significant difference in sex distribution (74% vs 67% females, p=0.24). PCA and Bonferroni-adjusted ANOVA identified proconvertase furin as the most robust biomarker signature for POTS. Plasma level of proconvertase furin was lower (6.38 vs. 6.58 of normalised protein expression units (NPX); p<0.001 in POTS, compared with the reference group. Proconvertase furin met Bonferroni-adjusted significance criteria in both uni- and multivariable regression analyses. Conclusion: Patients with Postural Orthostatic Tachycardia Syndrome have lower plasma level of proconvertase furin compared with individuals with normal postural hemodynamic response. This finding suggests the presence of a specific autoimmune trait with disruption of immune peripheral tolerance in this hitherto unexplained condition. Further studies are needed for external validation of our results.